Leisure time physical activity among employed and unemployed women in Poland - Elżbieta Biernat; Monika Piątkowska (SAGE Publishing, 2017)
Objective/Background: The aim of the paper was to investigate the leisure time physical activity (LTPA) among Polish employed and unemployed women in light of meeting the World Health Organisation (WHO) recommendations and analysed its relationship with employment status. The concept of personal responsibility for a healthy lifestyle plays in the modern times a crucial role here and is an integral part of the prevention process (including the necessity for LTPA). Methods: A sample (n=527) of Polish women was surveyed by the long form of International Physical Activity Questionnaire (IPAQ-LF), with statistically significant differences between variables (intensity and duration of the activity vs. employment status), in the model being verified by chi-square testing. Multi-variable logistic regression analysis was performed to find the relationship between socio-demographic criteria and the amount of exercise recommended by WHO. The relationship between LTPA and the amount of exercise recommended by WHO was assessed using the log-linear analysis. Results: Over one-third of the respondents did not engage in any LTPA (employed - 38.6 and unemployed - 36.6%). Employed women engaged in vigorous exercises more often (18.2%) than those who were unemployed (5.8%). The amount of LTPA undertaken by the majority of respondents (58.7% employed and 65.2% unemployed) was not sufficient to maintain their health owing to lack of walking, moderate and vigorous LTPA. Conclusion: Polish women nowadays (regardless of whether they are employed or not) still do not engage in a sufficient amount of LTPA to maintain their health. Intervention programme in both groups is needed.